Pengembangan Perangkat Pembelajaran Gerak Dasar Pencak Silat Melalui Pendekatan Taktis di Sekolah Menengah Pertama Negeri 1 Salimpaung - sasmitha, weny; Suwirman, Suwirman (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
The learning activities about basic moves of Martial Art at class VII of SMPN 1 Salimpaung were not optimally done yet. As a result, the expected learning outcomes were not succesfully obtained. Thus, a new instructional design needs to be developed. This research apllied the ADDIE model that consisted of five phases : analysis, design, development, implementation, and evaluation. The learning model used was the tactical model. A syllabus, lesson plans, handouts, and a learning implementation guide were developed in this research. The instruments used were interviews, observation, validation questionnaires, and a test to measure the learning outcomes. The data were analyzed by using the qualitative and quantitative descriptive analysis. The research result shows that instructional design was valid, practical, and effective to be applied in the learning process.